Whole-genome sequences of Colletotrichum siamense and Colletotrichum truncatum, causal agents of pod and foliar diseases on African yam bean - Ogunsanya, O.M.; Armitage, A.D.; Afolabi, C.G.; Oyatomi, O.; Thompson, E.P.; Ortega-Beltran, A.; Abberton, M. (American Society for Microbiology, 2024)
Diseases caused by Colletotrichum fungi result in major agricultural losses worldwide. Here, we present two draft genomes of Colletotrichum spp. responsible for foliar and pod blight on African yam bean. Colletotrichum siamense and Colletotrichum truncatum assemblies totalled 55.8 Mb in 563 contigs and 54.8 Mb in 1,240 contigs, respectively.